FORMULASI PENDIDIKAN VOKASI MELALUI PROGRAM KETERAMPILAN PADA MADRASAH ALIYAH PLUS KETERAMPILAN DI ACEH - Andhika, M. Rezki; Hamdi, Syaibatul (Program Studi Pendidikan Agama Islam Sekolah Tinggi Agama Islam Negeri (STAIN) Teungku Dirundeng Meulaboh Aceh Barat, 2024)
This article discusses the urgency of developing vocational education in Madrasah Aliyah in Indonesia, especially in Aceh Province, which is facing the challenges of the Industry 4.0 era. Indonesia has great potential in natural resources and cultural diversity, but it needs quality and globally competitive human resources to optimize it. Despite Indonesia's great economic potential, the quality of human resources is still an issue. The government has responded to this issue with policies, including improving Madrasah Aliyah Plus Skills. This research is field research using a descriptive qualitative method. This research was conducted on all Madrasah Aliyah plus skills in the Aceh Province area: MAN 3 Banda Aceh City, MAN 1 North Aceh, MAS Seunuddon, and MAN 1 Langsa City. The data collection techniques used are observation, interview, and document review. The informants in this research include Madrasah Heads, Teachers or Vocational Instructors, Instructor Assistants, Curriculum Officers, and students. The data analysis includes data reduction activities, data presentation, and conclusion drawing and verification. The implementation of Vocational education in Madrasah Aliyah plus skills requires substantial support, especially in the development of a curriculum that follows industry needs. The main challenge of Madrasah Aliyah Plus Skills is to ensure that the curriculum is relevant to the needs of the local industry. The Teaching Factory has been implemented to train students with practical skills needed in the world of work. The importance of strengthening partnerships with the business world and industry was also highlighted to provide job opportunities for graduates. Improving the quality of vocational education at Madrasah Aliyah Plus Skills in Aceh not only provides benefits for students but also for regional and national economic growth.